The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1159/000345942
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Intraoperative Imprint Cytology in Ovarian Germ Cell Tumors

Abstract: Objective: This study retrospectively investigated the usefulness of intraoperative diagnosis based on imprint cytology and frozen sections for ovarian germ cell tumor. Study Design: Intraoperative studies were reviewed for 23 cases with ovarian germ cell tumor treatment for which both frozen sections and imprint cytology were available. Final histopathologic diagnoses were compared with those based on intraoperative examinations. Results: Underlying pathologies included dysgerminoma (n = 6), yolk sac tumor (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Imprint cytology is reportedly useful in the diagnosis of ovarian germ cell tumors. 14 The imprint cytology of dysgerminoma is characterized as a so-called "two-cell pattern," containing atypical cells and lymphocytes. 14 Gonadoblastoma is not easily confused histopathologically with other gonadal neoplasms; the differential diagnosis includes sex cord tumors with annular tubules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Imprint cytology is reportedly useful in the diagnosis of ovarian germ cell tumors. 14 The imprint cytology of dysgerminoma is characterized as a so-called "two-cell pattern," containing atypical cells and lymphocytes. 14 Gonadoblastoma is not easily confused histopathologically with other gonadal neoplasms; the differential diagnosis includes sex cord tumors with annular tubules.…”
Section: Discussionmentioning
confidence: 99%
“…14 The imprint cytology of dysgerminoma is characterized as a so-called "two-cell pattern," containing atypical cells and lymphocytes. 14 Gonadoblastoma is not easily confused histopathologically with other gonadal neoplasms; the differential diagnosis includes sex cord tumors with annular tubules. The differential diagnosis of dysgerminoma, on the other hand, includes poorly differentiated carcinoma, diffuse large B-cell lymphoma, and embryonal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that imprint cytology of malignant ovarian tumors showed a high degree of nuclear atypia and highly cellular clusters [11,12] . Although these features were also observed in malignant Brenner tumors, nuclear grooves were not seen in other malignant ovarian tumors.…”
Section: Discussionmentioning
confidence: 99%
“…68 The cytomorphology of germ cell tumors varies with the type. 125 Dysgerminoma Dysgerminomas are the most common malignant germ cell tumor of the ovary, and comprise 1-2% of all malignant ovarian tumors. 124 Intraoperative imprint cytology may aid in the correct diagnosis of germ cell tumors as they allow for more thorough sampling of the tumor than a single frozen section.…”
Section: Germ Cell Tumorsmentioning
confidence: 99%